IMPLEMENTASI SISTEM PENGENDALIAN INTERNAL PADA PERUSAHAAN JASA - Wahyu Wahyu Wahyu; Marliyati Marliyati Marliyati; I. Nyoman Romangsi (Politeknik Negeri Semarang, 2019)
The aim of this article is to analyze internal control in service company. The analyze used the components of internal control according to COSO: control environment, risk assessment, control activities, information and communication, monitoring. Analysis of internal control used the data obtained through observation, questionnaires, interview, and documentary. Based on this analysis results can be concluded, that the dual positions refer with company SOP (Standard Operating Procedure). Separation of task does not work because that the dual positions. Therefore, the component of control activities applied at company is not in accordance with the component of control activities according to COSO. Nonconformity components still results in very effective internal control because the purpose of the internal control still remains to be achieved even though there are components that are not in accordance with the internal control components according to COSO.